ANGPTL3 and residual atherosclerotic risk: from lipid metabolism to therapeutic targeting - Weng, Shuwei; Ding, Chen; Lin, Jinxiu; Chai, Dajun (Frontiers in Endocrinology, 2026)
Despite achieving recommended low-density lipoprotein cholesterol (LDL-C) targets, many patients remain at high risk of cardiovascular events due to elevated triglyceride-rich lipoproteins and remnants. Angiopoietin-like protein 3 (ANGPTL3) has emerged as a promising therapeutic target for addressing this residual risk. As a liver-secreted regulator of lipoprotein metabolism, ANGPTL3 influences triglycerides, LDL-C, and high-density lipoprotein cholesterol through inhibition of lipoprotein lipase and endothelial lipase. Human genetic studies and pharmacologic interventions consistently show that ANGPTL3 inhibition improves lipid profiles and lowers apolipoprotein B–containing lipoproteins, independent of LDL receptor function. This review integrates biological, genetic, and clinical evidence, and provides an overview of novel ANGPTL3-targeted therapies, offering new perspectives for cardiovascular prevention and lipid management.